Suitability of virtual reality for simulating smoking among current mild cigarette smokers in Chennai city - Monica Gurupriya Mohanram; P D Madankumar (Wolters Kluwer Medknow Publications, 2022)
Background: Multi-component psychological interventions have proven broadly to be effective for smoking cessation. Cue-induced craving is considered responsible for relapse after smoking cessation. Cue Exposure Therapy (CET) consists of controlled and repeated exposure to stimuli associated with substance use to extinguish craving responses. A recent mode of cue presentation that has received increasing attention in the literature is the use of virtual reality (VR). VR uses computer-based technology to generate three-dimensional environment that allows people to move through their surroundings and interact with the created environment. The aim of our study was to determine the suitability of VR for simulating smoking among current cigarette smokers in Chennai city. Materials and Methods: A cross-sectional study was conducted with a purposive sample of 40 truck drivers above 18 years of age. Sense of satisfaction experienced by participants after completion of one VR session was assessed at the end of the experiment using suitability evaluation questionnaire (SEQ). Results: The mean age of the participants was 47.23 ± 12.43 ranging from 19 to 74 years. The suitability of VR for simulating smoking among current mild cigarette smokers according to the SEQ scale showed intermediate suitability. Conclusions: The result of the present study showed that VR environments that simulate real situations are suitable to elicit craving and thus assist in smoking cessation.